The Role of Leadership in Managing Information Technology Change and its Impact on Organisational Human Resources - HM, Manda; Abidin, Andi Zainal (PT. LITERASI SAINS NUSANTARA, 2023)
The development of information technology (IT) has significantly changed the way organisations operate and communicate. In the digital era, organisations that want to remain competitive and relevant must be able to manage information technology changes well. The purpose of this study is to examine the role of leadership in managing information technology change and its impact on organisational HR. This research is a literature review that utilises qualitative methods, which means that it will analyse and interpret data by utilising information and text derived from various sources. The results of the study show that the role of leadership in managing information technology change is very important in the ever-evolving digital era. Leaders must have a deep understanding of technology, formulate a digital transformation strategy, and guide the organisation through the change. The impact of effective leadership is increased productivity, innovation, and organisational competitiveness. However, technological change also impacts the organisation's people, and leaders must ensure that people have the necessary skills and knowledge, and create a culture that supports innovation and continuous learning.